Bilateral Inguinal Hernia Repair: Laparoscopic Totally Extraperitoneal Versus Open Lichtenstein - Yosypenko, Mykhaylo; Shulyarenko , Oleg V.; Havrylov, Hryhorii O. (Acta medica Lituanica, 2025)
Aim: To compare the outcome of laparoscopic totally extraperitoneal repair versus the open Lichtenstein technique in the treatment of primary bilateral inguinal hernias.Materials and methods: The study design was comprised of a matched and randomized research: a total of 93 patients were enrolled in the study and operated in clinic “Medikom” from 2015 to 2022. The patients were prospectively randomized and divided into two groups: Group 1 (n=45) underwent TEP repair, whereas Group 2 (n=48) received Lichtenstein repair.Result: No statistically significant differences were observed between the groups concerning the mean age, sex, body mass index, patient distribution by hernia type, European Hernia Society hernia type, and ASA score (p>0.05).The operating time in Group 1 was on 10.7% more than in Group 2 (p<0.05). At 6 hours post-surgery, the pain score in Group 2 was 1.19-fold significantly higher than in Group 1 (p<0.05). This significant difference persisted at 24 hours post-surgery, with Group 2 exhibiting a pain score 1.27 times greater than Group 1 (p<0.05). The time to resumption of normal activities was 1.5 times longer in Group 2 compared to Group 1, which is a difference that reached statistical significance (p<0.05). No statistically significant difference was observed regarding the incidence of early complications between the two groups (p>0.05 (χ2-test)). Following a 24-month follow-up period, a total of 42 (93.3%) patients from Group 1 and 45 (93.75%) patients from Group 2 were evaluated. Importantly, neither recurrence nor other complications were observed in either group.Conclusions: The findings of this trial indicate that laparoscopic total extraperitoneal (TEP) hernia repair offers substantial benefits for patients undergoing bilateral inguinal hernioplasty. The duration until resumption of normal activities was 1.5 times significantly longer for patients in the open hernia repair Group 2 compared to those in the laparoscopic hernia repair Group 1.